Synthesis and characterization of glass fiber grade specimen using different source of Kaolin - Tan, Yan Jun (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
This report is mainly concentrating on the synthesized and characterization of glass fiber using 2 different kind of kaolin. The kaolin inquiry from different resources obtained the variable in term of AlO3/SiO2 ratio and different trace content and it might directly or in directly affect the properties of the glass such as rheology characteristic, thermal behavior, colour of the glass and mechanical properties such as the hardness. The main objectives of this study are to investigate how different source of kaolin give significant affect to the glass characteristic..